Load characteristics in process modules of offshore platforms under jet fire: The numerical study. (May 2017) - Sun, Liping; Yan, Huibin; Liu, Songhua; Bai, Yong
Abstract: Jet fire represents a major fire risk in process modules of offshore oil & gas platforms. The heat loads generated by jet fire in these areas may lead to significant consequences and needs to be studied thoroughly. This paper focuses on the load characteristics in process modules of offshore platforms under jet fire conditions. FDS code is chosen to model different jet fire scenarios. Firstly, results of published experiment are chosen to validate the jet fire simulation method. Then, typical jet fire scenarios in an example process module of offshore platforms are studied. Valuable suggestions for modelling jet fire scenarios in process modules are given and load characteristics for the jet fire scenarios mentioned above are shown in this paper. The effects of different parameters on load characteristics of the considered scenarios are also discussed. The jet fire modelling method and the results of the studied scenarios can provide valuable references for similar scenarios in engineering. Highlights: This paper focuses on the load characteristics in process modules of offshore platforms under jet fire. Jet fire with methane fuel is studied here. FDS code is utilized to model different jet fire scenarios. The jet fire simulation method based on FDS code is validated to be suitable. Valuable suggestions for modelling jet fire scenarios in process modules are given and load characteristics for the jet fire scenarios mentioned above are shown in this paper. The effects of different parameters on load characteristics of the considered scenarios are also discussed. The jet fire modelling method and the results of the studied scenarios can provide valuable references for similar scenarios in engineering.